2018
DOI: 10.1002/mc.22932
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive activity of PIWI‐interacting RNA in human fibrosarcoma mediated through repression of RRM2

Abstract: P‐element induced wimpy testis (PIWI)‐interacting RNAs (piRNAs) are a promising class of small regulatory RNAs, earlier believed to control transposable elements (TEs) activity in germlines are now reported in somatic and cancer cells. The aberrant expression of piRNAs has been documented in various cancers wherein they modulate tumorigenesis either as oncogenes or tumor suppressors by curbing target gene expression. However, there is no report yet on the association of piRNAs in fibrosarcoma, an early metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 65 publications
(166 reference statements)
0
42
0
Order By: Relevance
“…Notably, our previous study has revealed that piR‐39980 is downregulated in fibrosarcoma cells and acts as a tumour suppressor in fibrosarcoma by targeting Ribonucleoside‐diphosphate reductase subunit M2 (RRM2) [Das et al., ], whereas current study revealed an opposite role for the piRNA as an oncogene in OS by targeting SERBINB1. To ensure its cancer‐type specific differential role, we checked the expression of RRM2 in OS cell lines by qRT‐PCR upon transfection with 80 nM piR‐39980 mimic and inhibitor.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, our previous study has revealed that piR‐39980 is downregulated in fibrosarcoma cells and acts as a tumour suppressor in fibrosarcoma by targeting Ribonucleoside‐diphosphate reductase subunit M2 (RRM2) [Das et al., ], whereas current study revealed an opposite role for the piRNA as an oncogene in OS by targeting SERBINB1. To ensure its cancer‐type specific differential role, we checked the expression of RRM2 in OS cell lines by qRT‐PCR upon transfection with 80 nM piR‐39980 mimic and inhibitor.…”
Section: Discussionmentioning
confidence: 55%
“…piR-55490 plays an inhibitory role in lung cancer by targeting mTOR signaling [24]. piR-39980 plays an inhibitory role in fibrosarcoma by repressing RRM2 [9]. However, the piRNAs expression profile in OSCC has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…piR-39980 exhibits anti-tumor effects in fibrosarcoma by repressing ribonucleotide reductase M2 subunit (RRM2) through direct binding at its 3'-untranslated region (UTR). However, this interaction is extensively complementary, which is different from the seed binding of microRNAs [9]. However, the expression profile of piRNAs in OSCC and their role in OSCC development and progression has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…All the reactions (miRNA and mRNA) were performed in triplicates and expression levels were calculated in terms of Relative normalized expression. The detailed protocol is provided in our previous study …”
Section: Methodsmentioning
confidence: 99%
“…The detailed protocol is provided in our previous study. 22 2.3 | Synthetic RNA oligonucleotides and transient transfection miR-197-3p mimic and scramble were purchased from Qiagen as RNA oligo. The 3´UTR of RAN (Gene ID: 5901) with miR-197-3p binding sites (GUGGUGAA) (wild-type, WT) and mutant (MUT) with four nts mutation (GGUGGUAA) were cloned into psiCHECK-2 vector (a gift from Dr. Beena Pillai, IGIB, New Delhi) having both firefly luciferase and Renilla luciferase.…”
Section: Quantitative Reverse Transcriptase Pcr Using Real-time Pcrmentioning
confidence: 99%